MILITÆR SÆDELIGHEDSLOVGIVNING I SAMSPIL MED DET CIVILE SAMFUND I 1700-TALLET - Kofoed, Nina Javette (Temp - tidsskrift for historie, 2012)
ABSTRACT Regulation of sexuality in military law in interaction with the civil society during the 18th century Sexual relationships constitute a field of interaction between civilian and military society. In the article it is argued that a decree in the Danish Articles of War of 1683, demanding soldiers to obtain the permission of their superior before getting married, was a way to ensure the lawful marriage of the soldiers, and not as former research has understood it, as a way to limit the number of married soldiers. In 1696 an ordinance gave impunity to certain groups of soldiers in first case of fornication. The ordinance is seen not as an acceptance of fornication, but as a compensation for the time spent trying to obtain permission from a superior; such delays in effect made a quick marriage in cases of pregnancy impossible for soldiers. By following the development of the military exemption from punishment for first case of fornication during the 18th century, the article shows how this exemption was extended firstly to more groups of soldiers and secondly to more than one case of fornication. A possible consequence was an unintended impact on the legitimacy of punishment for fornication and through that it had effects on civil law.